2021
DOI: 10.1111/epi.16995
|View full text |Cite
|
Sign up to set email alerts
|

Chronic limbic epilepsy models for therapy discovery: Protocols to improve efficiency

Abstract: Objective There have been recommendations to improve therapy discovery for epilepsy by incorporating chronic epilepsy models into the preclinical process, but unpredictable seizures and difficulties in maintaining drug levels over prolonged periods have been obstacles to using these animals. We report new protocols in which drugs are administered through a new chronic gastric tube to rats with higher seizure frequencies to minimize these obstacles. Methods Adult rats with spontaneous limbic seizures following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…At least two studies have shown that with repeat dosing, levetiracetam rapidly loses its efficacy, even with high doses. 30,31 There are also studies that demonstrate that with longer term dosing, a pattern of incomplete response can be seen over several weeks of chronic treatment. Using existing models over the longer term may allow researchers to develop new insights into the effects of drugs on epilepsy and to analyze the timedependent or chronic aspects of how epilepsy medications lose their efficacy or cause toxicity.…”
Section: Effects Of a Drug On Seizures Over Timementioning
confidence: 99%
“…At least two studies have shown that with repeat dosing, levetiracetam rapidly loses its efficacy, even with high doses. 30,31 There are also studies that demonstrate that with longer term dosing, a pattern of incomplete response can be seen over several weeks of chronic treatment. Using existing models over the longer term may allow researchers to develop new insights into the effects of drugs on epilepsy and to analyze the timedependent or chronic aspects of how epilepsy medications lose their efficacy or cause toxicity.…”
Section: Effects Of a Drug On Seizures Over Timementioning
confidence: 99%